Self-Efficacy and Task-Relevant Budgetary Participation on Managerial Performance through Transformational Leadership Style - Nurul Auliyah Safitri; Mahmud Mahmud; Risca Ariska Ramadhan (Advances in Management & Financial Reporting, 2026)
Purpose: This study aims to examine the effect of self-efficacy and task-relevant budgetary participation on managerial performance while analyzing the mediating role of transformational leadership among MSMEs in Dompu Regency. Research Method: An explanatory quantitative design was employed. Data were collected via questionnaires from 126 managers of halal-certified MSMEs, selected through purposive sampling. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized for data analysis. Results and Discussion: The findings reveal that self-efficacy and task-relevant budgetary participation have no direct significant impact on managerial performance. However, transformational leadership successfully and significantly mediates both relationships. This proves that individual psychological potential and participative budgeting processes require a visionary leader to be converted into actual managerial effectiveness. Implications: MSME stakeholders and policymakers should prioritize transformational leadership development programs rather than merely focusing on technical administrative training to optimize resource management and operational efficiency. Originality: This research highlights transformational leadership as an indispensable catalyst that bridges cognitive factors and participative control systems within the resource-constrained ecosystem of developing regional MSMEs.